The Director's Role in the Community Service Advertisement “Titik Pulang” for the Al - Qomariah Islamic Boarding School Foundation - Cesa S, M. Ragil; Atmaja, Suhendra; Nihayati, Laila (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
An This study explores the role of the director in producing the public service advertisement